SISTEM PENJUALAN PPOB BERBASIS WEBSITE DAN TERINTEGRASI WHATSAPP GATEWAY STUDI KASUS KONTER PULSA - Muhamad Trisno; Hermansyah (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to design a PPOB (Payment Point Online Bank) system based on a website integrated with WhatsApp Gateway to improve the efficiency of the credit counter business. The research method includes data collection through interviews and literature studies, followed by system design using PHP, Node.js, HTML, and CSS. The results of the study show that the developed website facilitates online transactions such as purchasing electricity tokens, paying bills, and mobile phone credit, equipped with transaction history features and payment notifications. WhatsApp Gateway integration allows transactions via chat, increasing user accessibility. This system is expected to increase business productivity, customer convenience, and competitiveness in the digital era.